Targeting the Homologous Recombination Pathway in Cancer With a Novel Class of RAD51 Inhibitors - Gu, Peng; Xue, Liting; Zhao, Chunyan; Li, Wenjing; Jiang, Zhen; Liu, Aiguo; Li, Tingting; Liu, Lu; Decker, Markus; Cheng, Xiaoxuan; Yang, Wenqing; Tang, Renhong (Frontiers in Oncology, 2022)
Targeting DNA damage response (DDR) pathway has been proposed as an approach for amplifying tumor-specific replicative lesions. RAD51 plays a central role in the DDR process, and thus represents a promising anti-tumor target. We here report the discovery of a series of next generation RAD51 inhibitors that can prevent RAD51 foci formation. The lead compounds dramatically impaired human cancer cell growth, induced cell cycle arrest in S-phase, and resulted in elevated γH2AX. Furthermore, cancer cells became sensitized to chemotherapy and other DDR inhibitors. Dosed either as a single agent or in combination with cisplatin, the compounds significantly inhibited tumor growth in vivo. By upregulating ATR-CHK1 signaling, the RAD51 inhibitors increased surface PD-L1 levels in various tumor cells, suggesting a potential combination of RAD51 inhibitors with PD-1/PD-L1 blockade. Overall, our findings provide the preclinical rationale to explore RAD51 inhibitors as monotherapy or in combination with chemotherapy, immunotherapy or DDR-targeting therapy in cancer treatment.